Teadenol A in microbial fermented tea acts as a novel ligand on GPR120 to increase GLP-1 secretion. Issue 12 (13th November 2020) - Nagasawa, Tomotaka; Ishimaru, Kanji; Higashiyama, Shigeki; Hama, Yoichiro; Mitsutake, Susumu
Abstract : Post-fermented teas, produced by microbial fermentation, are attracting attention due to their health benefits that reduce the risk of hyperlipidemia and atherosclerosis. Abstract : Post-fermented teas, produced by microbial fermentation, are attracting attention due to their health benefits that reduce the risk of hyperlipidemia and atherosclerosis. Although several novel polyphenols have been identified from post-fermented teas, their biological activities have not yet been fully elucidated. In this study, we found that teadenol A, a polyphenol recently isolated from Japanese post-fermented tea, acts as a novel ligand on a long-chain fatty acid receptor, GPR120. Teadenol A activated GPR120 was over-expressed in 293T cells, and this activation was inhibited by the GPR120 antagonist AH7614. Additionally, teadenol A induced Erk1/2 phosphorylation and increased the intracellular Ca 2+ concentration in 293T cells, and these effects were completely dependent on GPR120 expression. Our results suggest that teadenol A binds and activates GPR120 directly. Furthermore, teadenol A enhanced the secretion of GLP-1 from intestinal endocrine STC-1 cells. GLP-1 suppresses appetite and increases insulin secretion, exhibiting anti-diabetic effects. GPR120/GLP-1 signaling is attracting attention as a potential target for pharmaceuticals against type 2 diabetes. Our results suggest that teadenol A is a key molecule in post-fermented tea responsible for beneficial effects on metabolic syndrome.